Tendons and Tendon Sheaths of the Hand – An Update on MRI - Schmitt, Rainer; Hesse, Nina; Grunz, Jan-Peter (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
Background The tendons of the hand run in close proximity to each other and within retinacular tunnels adjacent to articular joints, while forming intersections in characteristic locations. The enclosing tendon sheaths are often sites of systemic or infectious inflammation.Method This review article outlines the different entities of tendon and tendon sheath pathology and their manifestation in the hands. Diagnostic findings in tendon and tendon sheath disorders are illustrated using MRI imaging and discussed in context with the current literature.Results and Conclusion Overuse may cause stenosis in the fibrous outer layer of the retinacula and the A1 annular ligaments as well as tendinosis. In contrast, proliferative tenosynovitis is a disease of the synovial inner layer of the tendon sheath with tendon infiltration and tendinitis. Pyogenic tenosynovitis favors the flexor compartments. Because of the narrow spaces in the hand, a high-resolution MRI technique must be used.Key Points: Citation Format
Keywords: tendons; hand; fingers and toes; anatomy; inflammation; MR imaging